15-deoxy-[delta]12,14-prostaglandin J2 reinforces the anti-inflammatory capacity of endothelial cells with a genetically determined NO deficit - Urban, Ivelina; Turinsky, Martin; Gehrmann, Sviatlana; Morgenstern, Jakob; Brune, Maik; Milewski, Moritz R.; Wagner, Andreas H.; Rumig, Cordula; Fleming, Thomas; Leuschner, Florian; Gleißner, Christian A.; Hecker, Markus (Circulation research, 2019)
Rationale:Fluid shear stress (FSS) maintains NOS-3 (endothelial NO synthase) expression. Homozygosity for the C variant of the T-786C single-nucleotide polymorphism of the NOS3 gene, which solely exists in humans, renders the gene less sensitive to FSS, resulting in a reduced endothelial cell (EC) capacity to generate NO. Decreased bioavailability of NO in the arterial vessel wall facilitates atherosclerosis. Consequently, individuals homozygous for the C variant have an increased risk for coronary heart disease (CHD).Objective:At least 2 compensatory mechanisms seem to minimize the deleterious effects of this single-nucleotide polymorphism in affected individuals, one of which is characterized herein.Methods and Results:Human genotyped umbilical vein ECs and THP-1 monocytes were used to investigate the role of 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) in vitro. Its concentration in plasma samples from genotyped patients with CHD and age-matched CHD-free controls was determined using quantitative ultraperformance LC-MS/MS. Exposure of human ECs to FSS effectively reduced monocyte transmigration particularly through monolayers of CC-genotype ECs. Primarily in CC-genotype ECs, FSS elicited a marked rise in COX (cyclooxygenase)-2 and L-PGDS (lipocalin-type prostaglandin D synthase) expression, which appeared to be NO sensitive, and provoked a significant release of 15d-PGJ2 over baseline. Exogenous 15d-PGJ2 significantly reduced monocyte transmigration and exerted a pronounced anti-inflammatory effect on the transmigrated monocytes by downregulating, for example, transcription of the IL (interleukin)-1β gene (IL1B). Reporter gene analyses verified that this effect is due to binding of Nrf2 (nuclear factor [erythroid-derived 2]-like 2) to 2 AREs (antioxidant response elements) in the proximal IL1B promoter. In patients with CHD, 15d-PGJ2 plasma levels were significantly upregulated compared with age-matched CHD-free controls, suggesting that this powerful anti-inflammatory prostanoid is part of an endogenous defence mechanism to counteract CHD.Conclusions:Despite a reduced capacity to form NO, CC-genotype ECs maintain a robust anti-inflammatory phenotype through an enhanced FSS-dependent release of 15d-PGJ2.
Im Titel ist [delta] als griechischer Buchstabe dargestellt
Im Titel ist die Zahl 2 bei J2 tiefgestellt
Gesehen am 22.04.2020